MEKANISME PENYELESAIAN PERKARA PERSELISIHAN HUBUNGAN INDUSTRIAL DITINJAU DARI UNDANG-UNDANG NOMOR 2 TAHUN 2004 TENTANG PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL PADA PENGADILAN NEGERI KLAS IA SAMARINDA - Maryanto Maryanto; Wahyuni Safitri (Yuriska: Jurnal Ilmiah Hukum, 2018)
The relation between legal subjects such as person or legal entity in a case, frequently generates dispute. Along with the complexity of social life, then, the more parties are involved in the dispute, the wider scope of the dispute case. One of the concerned dispute in the society is Industrial Relations Disputes that become the competence of Industrial Relations Court. Since 2015, The Act No. 2/2004 about Industrial Relations Dispute Settlement has enforced effectively, it still has many weaknesses, wether from practical or regulation aspects. The legal problems of its Act cause the settlement of Industrial Relations Dispute become less effective and efficient, also hamper the principle of constante justitite (principle of rapid, fair and easy trial). The research concluded that the practical/operational level of the Judges Panel in examining and adjudicating the cases of Industrial Relations Dispute in Industrial Relations Court of Samarinda, which tend to apply the general civil procedure law, from the examination of legal standing of the parties, exception, interlocutory decision, replik, duplik, writen proof, the witnesses, experts/professional witnesses, conclusion and verdict. This procedures only prolong the examination and trial process to settle the case of Industrial Relations Dispute. Therefore, the SOP (Standard Operational Procedure) of the settlement of Industrial Relations Dispute cannot be well-implemented yet as the mandate of the law.